Insight into HIV-2 latency may disclose strategies for a cure for HIV-1 infection - Suha Saleh; Lenard Vranckx; Rik Gijsbers; Frauke Christ; Zeger Debyser (Elsevier, 2017)
HIV-1 and HIV-2 originate from two distinct zoonotic transmissions of simian immunodeficiency viruses from primate to human. Although both share similar modes of transmission and can result in the development of AIDS with similar clinical manifestations, HIV-2 infection is generally milder and less likely to progress to AIDS. HIV is currently incurable due to the presence of HIV provirus integrated into the host DNA of long-lived memory cells of the immune system without active replication. As such, the latent virus is immunologically inert and remains insensitive to the administered antiviral drugs targeting active viral replication steps. Recent evidence suggests that persistent HIV replication may occur in anatomical sanctuaries such as the lymphoid tissue due to low drug penetration. At present, different strategies are being evaluated either to completely eradicate the virus from the patient (sterilising cure) or to allow treatment interruption without viral rebound (functional cure). Because HIV-2 is naturally less pathogenic and displays a more latent phenotype than HIV-1, it may represent a valuable model that provides elementary information to cure HIV-1 infection. Insight into the viral and cellular determinants of HIV-2 replication may therefore pave the way for alternative strategies to eradicate HIV-1 or promote viral remission.